The Role of Financial Literacy and Household Economic Resilience in Community Service Programs in the Era of Global Uncertainty - Abdul Manap; Lilik Swarnata Angga Buana; Saut Pane; Diana Pujiningsih; Arko Pujadi (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2026)
Global uncertainty driven by economic changes, inflation, and the rapid development of digital technology has affected household economic stability across various social groups. These conditions have made financial literacy and household economic resilience increasingly relevant topics in community service programs. This study aims to analyze the role of financial literacy and household economic resilience in community service programs while expanding references related to community service in the field of community economic empowerment. The study employed a literature review method using a descriptive qualitative approach. Data were obtained from Google Scholar and several credible websites covering publications from 1964–2026. The initial search identified 50 articles, which were then strictly screened, resulting in 29 main articles used as analytical sources. The findings indicate that financial literacy influences people’s ability to manage income, control expenditures, and respond to household economic risks in a more adaptive and sustainable manner.